UC and BUC plane partitions - Shengyu Zhang; Zhaowen Yan (European Physical Journal C: Particles and Fields, 2024)
Abstract This paper is concerned with the investigation of UC and BUC plane partitions based upon the fermion calculus approach. We construct generalized the vertex operators in terms of free charged fermions and neutral fermions and present the interlacing (strict) 2-partitions. Furthermore, it is showed that the generating functions of UC and BUC plane partitions can be written as product forms.